STRATEGI DINAS KEBUDAYAAN DALAM PELESTARIAN WARISAN BUDAYA TAK BENDA (WBTB) DI PROVINSI RIAU TAHUN 2017 - Febriani, Ira (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The preservation of Intangible Cultural Heritage is a process of dynamic efforts to protect, develop, utilize and inherit culture, especially Malay Riau, which occupies the political geographical area of Riau Province, especially intangible heritage which can include oral literature, performing arts, celebrations, knowledge and behavior habits. regarding nature and the universe, skills and skills of traditional crafts and other activities that contain customary and cultural values in them.The purpose of this study is to describe the Preservation of Intangible Cultural Heritage by the Riau Provincial Cultural Office in 2017.The research approach used is a qualitative approach. This type of research is descriptive. The research location is at the Riau Provincial Cultural Office. Types and sources of research data are divided into primary data with purposive informant retrieval techniques and secondary data in the form of supporting data related to WBTB conservation. Data collection techniques used by interview and documentation. Meanwhile, data analysis was performed using qualitative analysis.The results of this study are that first, the conservation strategy carried out by the Riau Provincial Cultural Office in 2017 has been less than optimal where in carrying out its strategy related to WBTB Conservation has not shown a stage of perfection. Second, there are many obstacles faced in preserving WBTB in Riau Province.Keywords: Cultural Preservation, Intangible Cultural Heritage